Kinerja Baznas Kabupaten Siak Dalam Upaya Mengurangi Kemiskinan Menurut Undang-Undang Nomor 23 Tahun 2011 Tentang Pengelolaan Zakat - Supri Yadin Hasibuan (P3M dan Jurusan Syariah dan Ekonomi Bisnis Islam STAIN Sultan Abdurrahman Kepulauan Riau, 2022)
This paper lifting poverty problems experienced by lost of common people especially Moslems. They are oftentimes awfully underestimated due to their unrepresentative competence in establishing the economic power. zakat has a strategic potential which needs developing to be one of the income distributor instruments in Indonesia. So far, zakat potential in Indonesia has not yet been developed optimally as well as managed professionally. The reason is that the existence of zakat center is not effective pertaining collecting, distributing, administering, monitoring, as well as evaluating zakat. In other words, organizational system and zakat management up to this present time are still impressively conventional, consumptive, and inefficient, so there is no significant influence on society. With such reasons, the role of government is very important in solving zakat problems, through zakat center either in central office or regional office which is commonly called Regional Amil Zakat Center, it is really expected that zakat management can be working out optimally. The role of government, through regulation No. 23, 2011 in connection with zakat management to change through regulation No. 38, 1999, has spread positive impacts on Moslem society in managing zakat from muzakki (the giver). As a follow-up implementation of the regulation, Siak regency has issued Regional Regulation No. 6, 2013 concerning zakat, infaq, and shodaqoh management in Siak regency. With this kind of regulation, zakat management in Siak regency is more effective and efficient to reduce the amount of poverty.